Retailer-run resale market and supply chain coordination - Lee, Chang Hwan; Rhee, Byong Duk (International Journal of Production Economics, 2021)
This study proposes strategies for full coordination of a supply chain when the retailer enables buyers not only to return their product after inspection but also to resell it as used at the store after partial consumption. In recent years, mega-retailers have added resale service to their conventional business of selling new products, which is called the retailer-run resale market. Prior literature shows from the retailer's perspective that the ultimate motive for running resale business is to reduce the volume of consumers' product returns. Nevertheless, there is a lack of studies on the retailer's resale business from the manufacturer's perspective. We adopt a manufacturer's perspective and derive strategies to motivate retailers to make decisions for the benefit of the entire supply chain in the presence of the retailer-run resale market using five commonly used types of contracts: revenue-sharing, buybacks, quantity flexibility, quantity discount, and two-part tariff. Ongoing digitalization and web security in retailing have provided a convenient environment for online transactions, which have emerged as a supply chain and become a staple for many shoppers. However, growing popularity of online shopping inevitably increases the volume of product returns because it lacks an opportunity to experience the product before purchase. Thus, an increasing number of online retailers have adopted a resale business unilaterally to reduce consumer returns. The study provides strategic guidelines for a manufacturer to induce such retailers to make decisions for joint profit maximization.
Keywords: Chain management; Channel coordination; Mega-retailers; Partial consumption; Product returns; Quantity flexibility; Retailer-run resale market; Revenue-sharing; Supply chain coordination; Uncertainty of product value; Channel coordination; Product returns; Retailer-run resale market; Supply chain management; Uncertainty of product value